2013
DOI: 10.1371/journal.pone.0084194
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endogenous ENaC and TRP Channels in the Myogenic Response of Rat Posterior Cerebral Arteries

Abstract: AimsMechanogated ion channels are predicted to mediate pressure-induced myogenic vasoconstriction in small resistance arteries. Recent findings have indicated that transient receptor potential (TRP) channels and epithelial sodium channels (ENaC) are involved in mechanotransduction. The purpose of this study was to investigate the role of TRP channels and ENaC in the myogenic response. Our previous study suggested that ENaC could be a component of the mechanosensitive ion channels in rat posterior cerebral arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 41 publications
3
30
0
1
Order By: Relevance
“…DEG-like currents in cerebral arterial VSMCs were inhibited by ROS (257). ␤-ENaC in rat posterior cerebral arteries colocalized with TRPM4 but not TRPC6 (793,794), although all three channels participated in myogenic constriction.…”
Section: Renal Autoregulatory Mechanismsmentioning
confidence: 88%
“…DEG-like currents in cerebral arterial VSMCs were inhibited by ROS (257). ␤-ENaC in rat posterior cerebral arteries colocalized with TRPM4 but not TRPC6 (793,794), although all three channels participated in myogenic constriction.…”
Section: Renal Autoregulatory Mechanismsmentioning
confidence: 88%
“…The muscularis of the bladder is composed of smooth muscle, so one has to consider whether there is precedent for hyperthermia having a direct effect on perfusion of this organ. Activation of TRP (transient receptor potential) channels may be involved in regulating smooth muscle vasodilation upon heat stress [29,30]. Perfusion in tumours can increase as well by as much as 2-fold [27].…”
Section: Increased Perfusion May Remove Drug From Target Volumementioning
confidence: 99%
“…Recently, several studies reported that the requirement of ENaC proteins for myogenic response7823. In our previous studies, we also showed that the expression of ENaC protein and the effect of ENaC protein blockade with amiloride on myogenic response, and clarified that ENaC protein is critical for the mechanotransduction in the pressure-induced myogenic response1024. However, the ENaC protein has been suggested as mechanotransducer, the involvement of ENaC in the elevated myogenic response in hypertension has not been investigated.…”
Section: Discussionmentioning
confidence: 83%
“…The PCAs were cannulated with glass micropipettes, and perfused with K-H solution bubbled with a 95% O 2  + 5% CO 2 gas mixture to maintain a pH of 7.4 at 36 °C in an arteriograph system (Living Systems Instrumentation, Burlington, VT, USA) as previously described24. The lumen diameter of PCAs was recorded using the SoftEdge Acquisition Subsystem (IonOptix, Milton, MA, USA).…”
Section: Methodsmentioning
confidence: 99%